Correlations between intraretinal cystoid cavities and pre- and postoperative characteristics of eyes after closure of idiopathic macular hole - Goto, Kensuke (Sci Rep, 2020)
Intraretinal cystoid cavities have been detected at the edges of macular holes (MHs) but their clinical characteristics and their relationship to the MH variables have not been determined. We measured the areas of the intraretinal cystoid cavity in 111 eyes with MHs in the OCT images preoperatively. Our results showed that the intraretinal cystoid cavities were located in the Henle fiber layer-outer nuclear layer (HFL-ONL) complex in 106 eyes and in the inner nuclear layer (INL) in 89 eyes. All were resolved after the initial vitrectomy to close the MH. The mean area of the cystoid cavity was greater in the HFL-ONL complex (55.9 ± 42.7 × 10(3) μm(2)) than in the INL (9.1 ± 9.8 × 10(3) μm(2); P < 0.001). The area of the cystoid cavities was significantly correlated with the basal MH size (r = 0.465,P < 0.001), the external limiting membrane height (r = 0.793, P < 0.001), and the maximum retinal thickness (r = 0.757, P < 0.001). The area of the cystoid cavities was significantly correlated with the preoperative best-corrected visual acuity (BCVA; r = 0.361, P < 0.001), but not with the postoperative BCVA or the integrity of any of the outer retinal microstructural bands. The presence of intraretinal cystoid cavities was related to some morphological characteristics, but not to the postoperative BCVA or the restoration of the outer retinal bands.